Simulations of water flow in a horizontal and 900 pipe bend. (2022) - Kumar, Shivam; Kumar, Mukund; Samanta, Samiran; Ukamanal, Manoj; Pradhan, Asisha Ranjan; Prasad, Shashi Bhushan
Abstract: Pipe bends are prevalent in mechanical systems' pipeline networks. One of the most important features to consider when constructing a pipe network is head loss. In present paper water flow characteristics through horizontal and 90 0 pipe bend has been studied using CFD software at different velocities (0.5–3.5 m/s). The head loss in horizontal pipes is chiefly due to frictional forces, while head loss occurs in bends as a result of various of friction and bend impacts. Head loss through horizontal pipe and bend pipe increased with increase in velocity.